GSDMD-mediated pyroptosis restrains intracellular Chlamydia trachomatis growth in macrophages - Jiang, Ping; Chen, Hongzhi; Feng, Xiaojing; Xie, Huiqi; Jiang, Mengjie; Xu, Danning; Tang, Haoneng; Zhang, Ningjie; Chen, Jianlin; Zhang, Lei; Tang, Lingli (Frontiers in Cellular and Infection Microbiology, 2023)
Pyroptosis, a type of programmed necrosis associated with inflammatory, is a host defense mechanism against microbial infections. Although Chlamydia has been shown to induce pyroptosis, whether pyroptosis directly impacts the growth of Chlamydia has not been demonstrated. In this study, we found that C. trachomatis L2 infection of the mouse macrophage RAW 264.7 cells induced pyroptosis by monitoring the ultrastructural changes under transmission electron microscopy and the release of LDH and IL-1β. More importantly, this C. trachomatis-triggered pyroptosis with activation of caspases-1 and caspases-11 was also accompanied by gasdermin D (GSDMD) activation. Suppression of these two inflammatory caspases inhibited GSDMD activation. Interestingly, the C. trachomatis-triggered pyroptosis significantly inhibited the intracellular growth of C. trachomatis since inactivation of either GSDMD or caspase-1/11 significantly rescued infectious C. trachomatis yields, which suggests pyroptosis response can be utilized as an intrinsic mechanism to restrict C. trachomatis intracellular infection in addition to the well- documented extrinsic mechanisms by recruiting and enhancing inflammatory responses. This study may reveal novel targets for attenuating C. trachomatis infectivity and/or pathogenicity.